2021
DOI: 10.1111/pedi.13254
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes in prepubertal children

Abstract: Objective Puberty‐induced insulin resistance is considered critical in the pathogenesis of type 2 diabetes (T2D) in youth. The development of T2D before puberty suggests distinct risk factors and pathophysiology but, because of its rarity, this has not been well studied. We aimed to describe the clinical characteristics of children with T2D diagnosed before the onset of puberty. Research design and methods We retrospectively studied all children with autoantibody‐negative T2D and available pubertal development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Remarkably, the average ALT and AST levels for T1D were 20 U/L and 18.5 U/L, whereas the average AST and ALT levels for T2D were 48.6 U/L and 34.7 U/L, respectively. This supports the concept that patients with T2D are at higher risk of steatosis and developing nonalcoholic fatty liver disease [ 36 ]. Hemoglobin values remained consistent over the 3-year period.…”
Section: Discussionsupporting
confidence: 86%
“…Remarkably, the average ALT and AST levels for T1D were 20 U/L and 18.5 U/L, whereas the average AST and ALT levels for T2D were 48.6 U/L and 34.7 U/L, respectively. This supports the concept that patients with T2D are at higher risk of steatosis and developing nonalcoholic fatty liver disease [ 36 ]. Hemoglobin values remained consistent over the 3-year period.…”
Section: Discussionsupporting
confidence: 86%
“…T2D was diagnosed at age 12 or older in 74.8% of the children with T2D, but 25.2% were younger. A recent study has reported children diagnosed with T2D younger than age 10, although it is very uncommon [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a secondary analysis of deidentified data from chart reviews of children newly diagnosed with T1D (n=758) between 2008 and 2010 [ 8 ] or T2D (n=753) between 2016 and 2019 [ 9 ] at a large academic hospital in Houston, Texas. Diabetes type was clinically assigned by their pediatric endocrinologist.…”
Section: Methodsmentioning
confidence: 99%
“…The rapid β‐beta cell failure and the high morbidity seen in adolescent T2D underlines the need for prevention, early diagnosis, and aggressive treatment. The younger the child with T2D, the worse is the cardio‐metabolic profile 92 . Therefore, prevention and early identification of obesity, and simple fasting and post‐prandial BGL screening every 1–3 years, is especially important in LRS.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…The younger the child with T2D, the worse is the cardio-metabolic profile. 92 Therefore, prevention and early identification of obesity, and simple fasting and post-prandial BGL screening every 1-3 years, is especially important in LRS. Delay in diagnosis may result in presentation in DKA, which needs initial insulin treatment.…”
Section: Type 2 Diabetesmentioning
confidence: 99%